B52 promotes alternative splicing of Dscam in Chinese mitten crab, Eriocheir sinensis. Issue 87 (April 2019) - Wan, Zhi-Cheng; Li, Dan; Li, Xue-Jie; Zhu, You-Ting; Gao, Tian-Heng; Li, Wei-Wei; Wang, Qun
Abstract: B52 is a member of the classical serine/arginine (SR)-rich proteins, which are phylogenetically conserved and play significant roles in mRNA maturation, including alternative splicing. In the present study, the docking site, selector sequences and locus control region of the Chinese mitten crab ( Eriocheir sinensis ) Down syndrome cell adhesion molecule ( EsDscam ) were identified. Alternative splicing of Dscam is essential to generate different isoforms. We also isolated and characterised the B52 gene from E. sinensis ( EsB52 ). The 876 bp open reading frame of EsB52 encodes a 291 amino acid residue polypeptide, and EsB5 2 has two RNA recognition motifs (RRMs) at the N-terminus and an arginine/serine-rich domain at the C-terminus. Each RRM contains two degenerate short submotifs, RNP-1 and RNP2. Analysis of tissue distribution revealed that EsB5 2 mRNA expression was widespread in all tested tissues, and especially high in brain and hemocytes. In hemocytes, EsB52 was upregulated significantly after stimulation with pathogen-associated molecular patterns and bacteria. Furthermore, EsB52 RNAi decreased the number of Ig7 inclusion in mRNA rather than Ig2 or Ig3. Taken together, these findings suggest that EsB52 acts as an alternative splicing activator of EsDscam . Highlights: The alternative splicing mechanism of EsDscam was investigated. EsB5 2 mRNA expression is widespread, but highest in brain and hemocytes. EsB52 acts an alternative splicing activator of EsDscam .